RISK FACTORS AFFECTING SCABIES IN BAUBAU CITY - Agus Darmawan; Fitriani Fitriani; Taswin Taswin; Jusliana Jusliana; Wahyuddin Wahyuddin (Jurnal Riset Kesehatan, 2022)
Scabies is known as a contagious skin disease that attacks humans and animals. Data from the Baubau City Health Office of scabies has increased by 195 cases in January-May 2021. The purpose of this study was to determine the risk factors that influence the incidence of scabies in Baubau City. This type of research was a quantitative research with a case control approach, the number of samples is 92, with 46 case respondents and 46 control respondents. The technique for determining the number of samples was simple random sampling. Data processing using SPSS 22 with univariate and bivariate analysis. Based on the results of the bivariate analysis showed that knowledge p Value 0.0300.05 with OR value= 2.917, personal hygiene p Value 0.0350.05 with OR value= 2.731, and clean water facilities p-value 0.5720.05 with OR value= 1,622. The conclusion of this study was that there was an influence between knowledge and personal hygiene with the incidence of scabies and there was no effect of clean water facilities with the incidence of scabies in the working area of Betoambari Public Health Center.